Use of Evidence-Based Practice and Barriers to Utilize Research in Rural Social Work Practice. Issue 2 (3rd March 2016) - Lee, Mingun
Abstract : In this study the author explores the level of use of evidence-based practice and the extent of barriers to research utilization in rural practice settings. Ninety-one social work field instructors from the rural areas of Southeast Ohio reported moderate use of evidence-based practice in their treatment process. The majority of field instructors also identified significant barriers to research utilization in practice. In addition, the use of evidence-based practice was associated with barriers to utilize research in the areas of field instructors' characteristics, organizational settings and limits, and communication. Implications include suggestions for enhancing evidence-based practice in rural settings.